2007
DOI: 10.1111/j.1600-0838.2004.00399.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Fat in the Fire? Science, the News Media, and the “Obesity Epidemic”2

Abstract: In recent years, the “obesity epidemic” has emerged as a putative public health crisis. This article examines the interconnected role of medical science and news reporting in shaping the way obesity is framed as a social problem. Drawing on a sample of scientific publications on weight and health, and press releases and news reporting on these publications, we compare and contrast social problem frames in medical science and news reporting. We find substantial overlap in science and news reporting, but the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
177
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(186 citation statements)
references
References 44 publications
4
177
0
5
Order By: Relevance
“…This approach contrasts with the majority of body-size stigma research that focuses on the stigmatization of large bodies and analyzes body-size stigma victims' recollection of stigmatizing messages (Cossrow, Jeffery, & McGuire, 2001;Puhl, Moss-Racusin, Schwartz, & Brownelll, 2008) or analyzes media discourse about weight (Heuer et al, 2011;Saguy & Almeling, 2008;Saguy & Riley, 2005). In addition, analyzing SC generated by lay individuals adds critical knowledge to the field of stigma research, since previous research indicates that body-size stigma is pervasive (Puhl & Brownell, 2003), but getting participants to admit to feeling stigma toward an individual or group is difficult, and capturing the ways that such stigma is communicated is especially challenging (Bresnahan & Zhuang, 2010).…”
Section: Study Rationalementioning
confidence: 98%
See 1 more Smart Citation
“…This approach contrasts with the majority of body-size stigma research that focuses on the stigmatization of large bodies and analyzes body-size stigma victims' recollection of stigmatizing messages (Cossrow, Jeffery, & McGuire, 2001;Puhl, Moss-Racusin, Schwartz, & Brownelll, 2008) or analyzes media discourse about weight (Heuer et al, 2011;Saguy & Almeling, 2008;Saguy & Riley, 2005). In addition, analyzing SC generated by lay individuals adds critical knowledge to the field of stigma research, since previous research indicates that body-size stigma is pervasive (Puhl & Brownell, 2003), but getting participants to admit to feeling stigma toward an individual or group is difficult, and capturing the ways that such stigma is communicated is especially challenging (Bresnahan & Zhuang, 2010).…”
Section: Study Rationalementioning
confidence: 98%
“…Contemporary popular and medical discourse about body size emphasizes individual responsibility for weight and simultaneously highlights the individual and societal financial costs associated with "unhealthy" weighttypically obesity (Saguy & Almeling, 2008;Saguy & Riley, 2005). Smith (2007a) postulates that SC will often assign personal responsibility for the condition to the individual and/or attribute significant social peril (i.e., a costly burden to society) to the condition.…”
Section: Study Rationalementioning
confidence: 99%
“…For example, it is reported that the media portrayals have increased, consistently present obesity in a negative tone and suggest that obese people need 'remedial action' [29][30].…”
Section: Obesity Discrimination In the Workplacementioning
confidence: 99%
“…News reports on health topics reflect widely-held attitudes and also potentially shape attitudes about health risk and health policy (Gollust et al, 2012;Gollust et al, 2013;Saguy and Almeling, 2008). Exposure to some sorts of news media representations of health and illness may also have unintended consequences, such as worsening the stigma associated with certain health risks.…”
mentioning
confidence: 99%